The Implementation of Genre-Based Approach Through Project-Based Learning in Teaching Writing - Khasanah, Nur; Faridi, Abdurrachman; Wahyuni, Sri (Universitas Negeri Semarang, 2023)
Writing is one of the six elements of English in the Emancipated Curriculum that must be mastered by Phase E (10th-grade) students. It is a productive skill that proves challenging for students. Considering this, a genre-based approach and project-based learning will be the best techniques for the teacher and students to achieve the learning target. This study aimed to explain the implementation of a genre-based approach through project-based learning in teaching writing. The research design was a qualitative case study conducted at SMKN 1 Temanggung. The participants of this study were thirty-six students and one English teacher. The instruments used in this study were observation class, interview, questionnaire, and document review. The data were analyzed using an interactive analysis model based on Miles and Huberman (1994). The results show that the planning stage of using a genre-based approach through project-based learning was found in the teaching documents (the syllabus, lesson plan, and learning materials), the practice of using a genre-based approach through project-based learning was manifested in the teaching and learning activities, and the assessment of using it was conducted through formative assessment by giving the written test and work performance. So, it was concluded that the use of a genre-based approach through project-based learning was implemented in teaching writing. This holistic study contributes significantly to the understanding of effective pedagogical practices, providing a unique perspective on combining these approaches to enhance students' writing skills. It underscores the potential of this combined approach, offering a valuable contribution to the field of language education, especially in teaching writing skills.